International Standards for Symphysis-Fundal Height Based on Serial Measurements From the Fetal Growth Longitudinal Study of the INTERGROWTH-21st Project: Prospective Cohort Study in Eight Countries. Issue 3 (March 2017) - Papageorghiou, Aris T.; Ohuma, Eric O.; Gravett, Michael G.; Hirst, Jane; da Silveira, Mariangela F.; Lambert, Ann; Carvalho, Maria; Jaffer, Yasmin A.; Altman, Douglas G.; Noble, Julia A.; Bertino, Enrico; Purwar, Manorama; et al.
Abstract : (Abstracted from BMJ 2016;355:i5662) Fetal growth assessment is important to identify fetuses with abnormal fetal growth that are at increased risk of perinatal morbidity and mortality. Serial measurement of symphysis-fundal height (SFH) is the recommended, inexpensive, and first-level screening tool in both low- and high-risk pregnancies.